Analyzing Code-Mixing and Code-Switching in Teacher Discourse in Arabic Language Education - Zakiyyah Ambarwati Sutarni; Toto Edidarmo; Hafiz Muhammad Amin (Penerbit Minhaj Pustaka, 2026)
This study aims to describe the use of code-switching and code-mixing in Arabic language learning and to identify the factors that influence teachers to use code-mixing and code-switching when teaching Arabic. The study uses a descriptive method with a qualitative approach. The subjects of this study were 30 students in class 11 1 and 27 students in class 12 E at MAN 5 Bogor Regency. Data were obtained through classroom observation to identify forms of code-switching and code-mixing, as well as teacher interviews to find out the factors causing the use of code-mixing and code-switching. The research data were analysed using qualitative descriptive analysis. The results showed that teachers used interlingual code-switching 70 times, intralingual code-switching 20 times, and tag switching 26 times, as well as code-mixing in the form of outer code mixing 125 times and inner code mixing 12 times.